Randomized Controlled Trial of Vinyl Bags versus Thermal Mattress to Prevent Hypothermia in Extremely Low-Gestational-Age Infants - Mathew, Bobby; Lakshminrusimha, Satyan; Sengupta, Shaon; Carrion, Vivien (American Journal of Perinatology, 2013)
Objective To compare the efficacy of vinyl bags and thermal warming mattresses in preventing hypothermia during delivery room resuscitation and stabilization of extremely low-gestational-age neonates (ELGANs).Study Design Preterm infants 23 to 28 weeks' gestational age were randomly allocated to either vinyl bag or thermal mattress group at delivery to prevent hypothermia. The primary outcome of the study was the axillary temperature on admission to the neonatal intensive care unit.Results A total of 41 infants were enrolled in the study. The mean admission temperature in the vinyl bag group was 36.1°C ± 0.7°C as compared with 35.8°C ± 1.3°C in the thermal mattress group. The subgroup of these infants with lower birth weight (<750 g) had significantly higher admission temperature with vinyl bags (36°C ± 0.4°C) compared with thermal mattress (35°C ± 1.3°C).Conclusion Vinyl bags and warming mattress are equally effective in improving admission temperature in ELGANs. Improvements in other areas such as delivery room temperature may be needed to achieve the goal of preventing hypothermia in this vulnerable population.
Keywords: hypothermia; prematurity; vinyl bags; warming mattress